The Semiotic Immersion of Video Games, Gaming Technology and Interactive Strategies - Neiva, Eduardo; Romano, Carlo (Public Journal of Semiotics, 2007)
The paper analyzes the effect of immersion in digital games using the theoretical apparatus of game theory. The paper illustrates interactive operations and the cause and effect relationship between player and designer, explaining the importance of strategic decision-making and pathing in player immersion. It considers the game function of creating a virtual world and proposes the idea that digital games are not just computer-mediated communication to the player. These games are games of “the moment”, like the game Chicken, and played with apparently great emotion, intelligence, and physical dexterity, although represented in software form. The relationship between the player and the computer is one of sign exchange, precisely the one that semiotics calls semiosis. The paper concludes that the personal achievement of individual players (end-users) accounts for the phenomenon of deep immersion in digital games. Not virtuality, but virtuosity is the strong force in digital game playing.